Santal religiosity and the impact of conversion : a staggering situation in socio-cultural development - Karim, A.H.M Zehadul (2012)
Santali religion is absolutely based on a traditional belief system of this ethnic group who has their strict adherence to their sanatoni (traditional) religious practices. But the Santals living in north-western part of Bangladesh have now been converted to Christianity in large numbers, and they have been seemingly formalized to a newly-evolved maladaptive religiosity. Traditionally speaking, the Santals had long been following their own religion which is certainly dissimilar from the Hindus or any other religious groups of South Asian communities. Since many years, the Santals in Bangladesh have had maintained their own sanatani practices without having any socio-political interference from their larger Bengali communities. But as time passes on, they now become the victim of circumstances, where the Santals have now become almost landless; and many of them have now been uprooted from their own settlement. In consequence, they migrate to the urban city centers, where the Santals seek employment in different Christian-based professional organizations. Being Christianized, the Santals usually change their parental names and instead, accept the new Christian names indicatively as a mark of religious compliance to their conversion. Interestingly however, it is found that the converters nevertheless retain their patronymic titles, having shown a king of ethnic attachment to their tradition and genealogy. This abrupt shift of religious allegiance of the Santals precariously put them in a world of contradiction and fluctuation with respect to their religious practices. This paper therefore explores as to what happens to their socio-cultural, religious and environmental adjustment in context of liminality and staggering situation.